Pengembangan Video Profil Sebagai Media Promosi Pada Pondok Pesantren - Wahyu Miftakhul Huda; Murhadi Murhadi; Wahju Tjahjo Saputro (Universitas Muhammadiyah Purworejo, 2023)
This study focuses on the development of profile videos. Where the research location of the education field had several attempts at promotion that had been applied by the society, including the creation of brochures, banners, and pamphlets. But some of the efforts made are still less effective. This is because promotion efforts already undertaken have a broader range and are easily accessible to the public.The issues of this study are solved using a voice-corrections application, adobe lightroom desktop for photo editing, shotcut software for video editing, and Windows 7 ultimate operating system. Hardware with a tripod, a DSLR camera, a handy camp, and a laptop. Primary data: the boarding house promotion at the Muhammadiyah junior high school village of Jono neighborhood graft district Purworejo.The results of the study were measured in terms of three aspects: social attraction, visualization of profile video content, and profiling media benefits. Public interest aspect assessments were achieved 78% of the 35 respondents. The visualizing aspect of the video profile of 76% of the 35 respondents. The visualizing aspect of the video profile of 76% of the 35 respondents. Of the 14 percent more than the average.